Effects of mulching with hyperaccumulator straw on growth and cadmium accumulation of accumulator Perilla frutescens. Issue 7 (27th May 2020) - Xiang, Gang; Lin, Lijin; Liao, Ming'An; Tang, Yi; Liang, Dong; Xia, Hui; Wang, Jin; Wang, Xun; Sun, Guochao; Zhang, Jing; Chen, Shengxiang; Zou, Yao; et al.
ABSTRACT: To study the effects of hyperaccumulator straw application on the growth and cadmium (Cd) accumulation of accumulator Perilla frutescens, four hyperaccumulator plant straws ( Youngia erythrocarpa, Galinsoga parviflora, Gnaphalium affine and Crassocephalum crepidioides ) were mulched on the surface of a Cd-contaminated soil (10 mg/kg) and P. frutescens seedlings were planted. The Y. erythrocarpa, G. affine and C. crepidioides straws increased P. frutescens root and shoot biomasses, and its chlorophyll a, carotenoid and total chlorophyll contents, whereas G. parviflora decreased or had no significant effect on these parameters. The G. affine and C. crepidioides straws enhanced the superoxide dismutase and catalase activities, and increased the Cd contents in roots and shoots of P. frutescens, whereas Y. erythrocarpa and G. parviflora straws had a smaller increasing effect. The Y. erythrocarpa, G. affine and C. crepidioides straws increased Cd extraction by P. frutescens shoots by 13.44%, 51.96% and 55.67%, respectively, compared with the control, whereas G. parviflora straw decreased it. Therefore, mulching with Y. erythrocarpa, G. affine and C. crepidioides straws could promote P. frutescens growth and enhance its phytoremediation ability for Cd-contaminated soil, with a better effect for G. affine and C. crepidioides straws than Y. erythrocarpa straw.